TLR Agonist Immunoadjuvants Provide Effective Protection Against PCV2 and PRV Infections in a Bivalent Subunit Vaccine for PCV2 and PRV - Fulai Yu; Wei Xiang; Weiye Ou; Yang Li; Xinbiao Shu; Xiaoliang Li (Veterinary Sciences)
Diseases associated with porcine circovirus type 2 (PCV2) and pseudorabies virus (PRV) significantly affect the economy of pig farms, particularly when combined infections lead to bacterial co-infections. Antigens from the pseudorabies variant strain gB and gD proteins and PCV2 (genotyped) Cap protein were mixed with the pattern recognition receptor (PRR) agonist FLICd as adjuvants and formulated with a micro-hydrogel adjuvant into PCV2 and PRV bivalent subunit vaccines. Twenty pigs, aged 30–35 days, were divided into groups A (received bivalent subunit vaccine) and B (received bivalent subunit vaccines with recombinant FLICd adjuvant), as well as C (non-vaccinated challenge control) and D (blank control). Groups A and B showed no significant difference in average daily weight gain compared to the unvaccinated controls. Fourteen days post-second vaccination, groups A and B exhibited significantly higher levels of PRV and PCV2 antibodies than groups C and D. Group B showed significantly higher average titers of PRV-specific neutralizing antibodies than group A. Fourteen days post-second vaccination, a PRV (ZJM-1 strain) challenge test was conducted. The vaccinated group achieved 100% protection. Vaccination effectively reduced virus load post-challenge and shortened the PRV shedding period. Vaccination with PCV2 and PRV bivalent subunit vaccines effectively prevents the onset of PCV2-related diseases and infections by wild pseudorabies strains.